Hubungan Indeks Massa Tubuh Dan Lama Anestesi Dengan Waktu Pulih Sadar Pada Anak Dengan General Anestesi Di Rumah Sakit Umum Daerah Kebumen Jawa Tengah - Yustiana Olfah; Reza Andisa; Sugeng Jitowiyono (LPPM STIKES Guna Bangsa, 2019)
The calculation of body mass index and duration of anesthesia is the first step of a series of actions performed anesthesia on pediatric patients who planned to undergo anesthesia . The calculation of body mass index and duration of anesthesia determine the smoothness of anesthesia , and the patient's recovery period after general anesthesia. The study is to determine the relationship of body mass index and duration of anesthesia with conscious recovery time after general anesthesia in children using observational analytic cross sectional survey approach. The site of research is in recovery room of The Central Surgery Installation RSUD Kebumen Central Java with as many as 44 research sample consists of body mass index and duration of anesthesia, with postoperative assessment instruments Steward score. The result is patients with conscious recovery time after general anesthesia slowly, over 30 minutes is a patient with a body mass index is not ideal that 13 people ( 68.42 % ) of the total sample whereas patients who recovered quickly in less than or equal to 30 minutes as many as 17 people ( 72 % ) with an ideal tubu mass index of the total sample . From the statistical test Chi-square computer program values obtained value , the probability asymp . Sig . ( 2 - sided ) : 0,008 which means there is a relationship of body mass index of anesthesia with the patient recovery time , and patients recover with time after general anesthesia consciously slowly , over 30 minutes is a patient with a long lebi anesthesia time of 1 hour 12 people ( 75 % ) of the total sample whereas patients who recovered quickly in less than or equal to 30 minutes of 20 people ( 71.43 % ) with a time of anesthesia faster than the total sample . From the statistical test Chi-square computer program values obtained value , the probability asymp. Sig. ( 2 - sided): 0,003 which means there is a long-standing relationship with the anesthesia recovery time of patients, so there is a relationship of body mass index and duration of anesthesia with conscious recovery time